Nonconforming Finite Element Method for the Obstacle Problem of the $p$-Laplacian (Advances in Applied Mathematics and Mechanics, 2025)
We consider the nonconforming discrete Raviart-Thomas mixed finite element method (dRT-MFEM) for obstacle problems with $p$-Laplacian differential operator. The a posteriori and a priori error analysis were presented in a new sense of measurement. A number of experiments confirm the effective decay rates of the proposed dRT-MFEM.